Legal Uncertainty Regarding Dual Certifications in Agrarian Law in Indonesia - Dewi Suryandari, Wieke; Sejati, Hono (International Journal of Law Social Sciences and Management, 2024)
Legal uncertainty regarding dual certificates in agrarian law in Indonesia is a significant problem that has the potential to cause prolonged land disputes. Dual certificates can arise due to inconsistencies in the land registration system, officers' negligence, applicants' negative intentions, and invalid administration. It creates uncertainty regarding ownership rights and reduces public trust in the land system. This study aims to analyze the legal uncertainty arising from dual certificates and their implications for legal certainty in agrarian law in Indonesia. In addition, this study also examines efforts that can be made to create legal certainty regarding dual certificates through improvements in the land registration system and the application of stricter legal principles. The research method used is normative juridical with a statutory approach and a conceptual approach. This study is expected to provide a deeper understanding of the problem of legal uncertainty related to dual certificates and solutions that can be applied to overcome this problem in agrarian law in Indonesia.